2017
DOI: 10.1007/s11255-016-1499-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender and dialysis adequacy on anaemia in peritoneal dialysis

Abstract: PurposeIn the general population, haemoglobin (Hb) concentration is higher in men than in women. However, target Hb levels in dialysis patients are set constant regardless of the patient’s sex. The aim of this study was to evaluate Hb concentration and the use of erythropoiesis-stimulating agents (ESA) in peritoneal dialysis (PD) patients taking gender and dialysis adequacy into account.MethodsThe study comprised two parts. The first was a cross-sectional analysis of Hb and ESA in 2180 prevalent PD patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Makruasi et al [ 48 ] conducted a comparable study on a larger patient group; they found that EPO hyporesponsiveness was 6.7% in their PD patient cohort, and that female gender was the predictive factor. In a large comparative study of PD patients, Ryta et al [ 49 ] found that women had significantly lower hemoglobin levels despite higher dialysis adequacy and higher doses of ESAs, and that gender was an independent determinant of ERI. Further large-scale cohort and comparative studies are required to explore the potential reasons for these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Makruasi et al [ 48 ] conducted a comparable study on a larger patient group; they found that EPO hyporesponsiveness was 6.7% in their PD patient cohort, and that female gender was the predictive factor. In a large comparative study of PD patients, Ryta et al [ 49 ] found that women had significantly lower hemoglobin levels despite higher dialysis adequacy and higher doses of ESAs, and that gender was an independent determinant of ERI. Further large-scale cohort and comparative studies are required to explore the potential reasons for these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these indices and body composition in general are different in males and females. Males also tend to produce more metabolites due to their larger body index, higher basal metabolism, and larger dietary intake, which combined with limited peritoneal clearance and residual renal function; these metabolites are not effectively cleared as they are in females, resulting in inadequate dialysis (17)(18)(19). However, the most recent ISPD guidelines set the target Kt/V level in dialysis patients as constant regardless of the patient's gender (8).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is a relationship between ESA resistance and dialysis adequacy [28]. Ryta et al [28] found a relationship between ESA resistance and Kt/V in adult patients on PD, while a relationship between Kt/V and ERI was found in HD patients in the study by Okazaki et al [9] and no relationship between them in the study by Gunnell et al [29].…”
Section: Discussionmentioning
confidence: 99%